Toward an Integrative Model of Effective FOB Succession - Le Breton–Miller, Isabelle; Miller, Danny; Steier, Lloyd P. (Entrepreneurship Theory and Practice, 2004)
Given that less than 10% of family owned businesses (FOBs) survive into the third generation, the issue of top executive succession has received a good deal of attention. Unfortunately, the literature on the topic is fragmented, as it deals with different parts of the elephant. This synthetic effort tries to put together the pieces to (1) derive a more encompassing model of what it takes for a succession to succeed, (2) determine the trends, consensus findings, as well as the gaps in our conceptual and empirical knowledge, and (3) suggest areas for further research.